The Evolving Landscape of Non-Traditional Learners in Higher Education: Trends, Strategies, and Institutional Responses - John C Chick Ed.D. (Adult Education Research Conference, 2025)
This research explores the characteristics of non-traditional learners, how they have evolved in recent years, and the strategies higher education institutions have employed to support this population. It also delves into the driving forces behind these changes and evaluates the efficacy of these strategies.
Keywords: adult learning; non-traditional learners; higher education